2002
DOI: 10.1007/3-540-45787-9_47
|View full text |Cite
|
Sign up to set email alerts
|

Building and Testing a Statistical Shape Model of the Human Ear Canal

Abstract: Abstract. Today the design of custom in-the-ear hearing aids is based on personal experience and skills and not on a systematic description of the variation of the shape of the ear canal. In this paper it is described how a dense surface point distribution model of the human ear canal is built based on a training set of laser scanned ear impressions and a sparse set of anatomical landmarks placed by an expert. The landmarks are used to warp a template mesh onto all shapes in the training set. Using the vertice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
(19 reference statements)
2
29
0
3
Order By: Relevance
“…and max ≈ 2.3 mm.. It is a well known fact that ear size and gender are related [7]. It is observed that the first mode of variation (P C1 shape ) of our shape model is related to size ( fig.…”
Section: Analysis and Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…and max ≈ 2.3 mm.. It is a well known fact that ear size and gender are related [7]. It is observed that the first mode of variation (P C1 shape ) of our shape model is related to size ( fig.…”
Section: Analysis and Resultssupporting
confidence: 51%
“…However, all of the above is based on manual measurements and manual registration, which is prone to error. A statistical shape model of the static ear canal based on scanned ear impressions and automated registration have been presented by Paulsen et al [7].…”
Section: Previous Workmentioning
confidence: 99%
“…Previous studies investigated the deformation of the ear canal and concha using calipers [2], and deformable shape models [3,4]. Yet, the relationship between deformations of the ear and clinical observations have so far not been explored.…”
Section: Prior Workmentioning
confidence: 99%
“…A method is developed for building statistical shape models based on a training set with an initial sparse annotation of corresponding landmarks of vary-ing confidence [14]. A model mesh is aligned to all shapes in the training data using the thin plate spline (TPS) transformation based on a few anatomical landmarks.…”
Section: Markov Random Field Correspondencesmentioning
confidence: 99%